2020
DOI: 10.2147/sar.s228224
|View full text |Cite
|
Sign up to set email alerts
|

<p>An Inverse Relationship Between Alcohol and Heroin Use in Heroin Users Post Detoxification</p>

Abstract: Background: Given that fewer than 50% of countries provide Opioid Agonist Maintenance Therapies (OAMT), it is important to assess whether other substances act as a substitute for heroin in recovering heroin users who receive detoxification models of treatment. There is a dearth of prospective studies from low-and-middle-income countries evaluating these patterns of substance use. Methods: 300 heroin users from the Gauteng province of South Africa were assessed on entry into inpatient detoxification and then fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…However, half of participants with no cannabis use at baseline were observed to have initiated use during follow-up. A similar pattern of initiating substance use during MMT follow-up has been reported in a study in South Africa in which alcohol use was found to increase in the initial period following MMT enrolment [ 43 ]. This could imply that some patients use may cannabis use to manage withdrawal symptoms as reported in some studies [ 26 , 27 ] although this finding has been disputed in another study [ 44 ].…”
Section: Discussionsupporting
confidence: 75%
“…However, half of participants with no cannabis use at baseline were observed to have initiated use during follow-up. A similar pattern of initiating substance use during MMT follow-up has been reported in a study in South Africa in which alcohol use was found to increase in the initial period following MMT enrolment [ 43 ]. This could imply that some patients use may cannabis use to manage withdrawal symptoms as reported in some studies [ 26 , 27 ] although this finding has been disputed in another study [ 44 ].…”
Section: Discussionsupporting
confidence: 75%
“…Study data were collected and managed using REDCap electronic data capture tools hosted at the University of the Witwatersrand ( 31 ). Further specifics of the study procedure are detailed in earlier publications of this study ( 32 , 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…3 The most common illicit opioid used in South Africa is heroin, 4 and South Africa is one of the top three regions in Africa most severely affected by opioid-related premature mortality. 5 A thriving drug trade, poor border control, and reduction of opioid cost have worsened the trend of opioid use. 4 ‘Nyaope’, also known as ‘whoonga’, ‘unga’ or ‘spices’, is the street name for a heroin-based drug that is currently ravaging urban and peri-urban communities of South Africa.…”
Section: Introductionmentioning
confidence: 99%